RGD-Labeled Hemocytes With High Migration Activity Display a Potential Immunomodulatory Role in the Pacific Oyster Crassostrea gigas - Lv, Zhao; Qiu, Limei; Wang, Weilin; Liu, Zhaoqun; Liu, Qing; Wang, Lingling; Song, Linsheng (Frontiers in Immunology, 2022)
Immunocyte migration to infection sites is important for host cellular defense, but the main types of migrating hemocytes and their mechanisms against pathogen invasions are unclear in invertebrates. In the present study, a population of hemocytes in the Pacific oyster Crassostrea gigas labeled with a fluorescein isothiocyanate (FITC)-conjugated Arg-Gly-Asp (RGD)-containing peptide was sorted. RGD+ hemocytes were characterized by smaller cell size and cytoplasmic-nucleo ratio, fewer cytoplasmic granules, and higher levels of myeloperoxidase, reactive oxygen species and intracellular free calcium concentration. RGD+ hemocytes exhibited a high level of migration activity, which was further induced after V. splendidus infection. Transcriptome analysis revealed that RGD+ hemocytes highly expressed a series of migration-related genes, which together with migration-promoting genes were significantly upregulated after V. splendidus infection. The neuroendocrine system was also proven to regulate the migration activity of RGD+ hemocytes, especially with the excitatory neuroendocrine factor dopamine, which promoted migration activity as confirmed by receptor blocking assays. Meanwhile, RGD+ hemocytes could highly express immunomodulatory factor interleukin (IL)-17s and their receptor genes, which was positively related to the production of antimicrobial peptides in whole hemocytes after V. splendidus infection. Collectively, this study identified a specific hemocyte population, i.e., RGD+ hemocytes, that shows high migration activity in response to pathogen infection, and exerts a potential immunomodulatory role by highly expressing IL-17s that might enhance the hemocytes antimicrobial peptides production in oysters.